2022
DOI: 10.1016/j.sleep.2021.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders and COVID-19

Abstract: This chapter summarizes the known associations between COVID-19 and sleep dysfunction, including insomnia, excessive daytime sleepiness, restless legs syndrome and nightmares, as well as obstructive sleep apnea and continuous positive airway pressure treatment during the pandemic. Treatment strategies and management approaches are also briefly discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 107 publications
6
78
0
6
Order By: Relevance
“…Additional polysomnography studies should be performed to investigate possible differences in sleep dynamics between groups. In some recent studies sleep disturbances during infection were observed, even in mild COVID-19 patients 45 47 may have implications for the results of HRV analyses. Changes in sleep dynamics during infection could also affect the number of arousals during sleep, as well as the number of U-shaped patterns.…”
Section: Discussionmentioning
confidence: 97%
“…Additional polysomnography studies should be performed to investigate possible differences in sleep dynamics between groups. In some recent studies sleep disturbances during infection were observed, even in mild COVID-19 patients 45 47 may have implications for the results of HRV analyses. Changes in sleep dynamics during infection could also affect the number of arousals during sleep, as well as the number of U-shaped patterns.…”
Section: Discussionmentioning
confidence: 97%
“…These outcomes agree with another study, where insomnia was referred to as “coronasomnia/COVID-somia”. Together with sleep fragmentation and nightmares, it became more frequent in the general population during the COVID-19 pandemic [ 42 ]. Interestingly, in a French study conducted by Kokou–Kpolou et al, in which diagnostic criteria for insomnia were met by 19.1% of the respondents, results were similar to the outcomes from the Italian population [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms of COVID-19 patients are varied, with the most common being fever, cough, digestive tract symptoms, sleep disorders and headaches, which are often treated by medication (Guan et al, 2020a;Bhat and Chokroverty, 2021;Fernández-De-Las-Peñas et al, 2021). Ibuprofen and acetaminophen are the most commonly used antipyretics.…”
Section: Symptomatic and Supportive Treatmentmentioning
confidence: 99%